Komunikasi Interpersonal Orang Tua Dengan Anak Penggemar Game Online Di Desa Tanjung Gusta Sunggal Kabupaten Deli Serdang - Syafitri, Nanda Lestari; Deni, Indira Fatra; Rozi, Fakhrur (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research aims to determine the impact of web-based games on children's interpersonal communication with parents and parental approaches to reduce dependency on internet games in Tanjung Gusta Sunggal, Deli Serdang Regency. Observations, interviews, and documentation were utilized in a qualitative descriptive research method. Symbolic interactionism theory was applied in this study. The findings of this research are related to how parents and children who enjoy playing online games communicate with each other. Children in Tanjung Gusta tend to display aggressive behavior towards those around them, especially when interacting with older individuals. They also tend to lose or make mistakes while playing online games. Moreover, they often defy their parents' orders solely for the sake of their online gaming pleasure. Because children believe that the gaming world is their realm, many of them spend more time playing online games than with their parents. Even when they attempt to be disobedient to assert that they are not children, adjustments can be made. It is not uncommon for them to utter dismissive words such as "ah" when receiving advice or reprimands from their parents. Parents should limit their children's time spent playing online games to no more than one or two hours per day to prevent them from becoming addicted. Choosing daytime hours, such as after school or in the evening before bedtime, is also recommended.